Use of ladderways in fragmented habitat to aid the movement of Japanese giant salamander (Andrias japonicus). Issue 2 (2nd April 2016) - Takahashi, Yoichi; Rashid, Md H.; Sarkar, Animesh; Asaeda, Takashi; Isono, Masanori; Omura, Tomohiro; Koga, Katsuyuki
ABSTRACT: The purpose of our study was to test whether different synthetic pathways affected the climbing behaviour of the Japanese Giant Salamander ( Andrias japonicus ). A preliminary survey was conducted to establish the primary status of existing individuals in the experiment area. As an artificial climbing passage, we selected ladders in four experimental conditions: the type of ladder (step-type vs. slope-type), the presence of wall with the ladder (present vs. absent), the water flow condition (flowing vs. non-flowing), and the position of the ladder in the experimental setup (left vs. right). Though the step-type ladder was more preferred by A. japonicus for climbing than the slope-type ladder, the most important factor that determined their preference was the presence of a side wall with the ladder. When there was no side wall, many salamanders fell off the ladder. Though more A. japonicus took ladders with flowing water than ladders with non-flowing water, the difference was not significant. For the climbing of A. japonicus, it did not matter whether the ladder was set on left or right side of the channel. This study suggests that any type of ladder along the sidewall with flowing water is suitable as a climbing passage for A. japonicus . This study reveals the possibility of using ladderways in small dams or weirs to aid movement of Japanese giant salamanders.